Perancangan Perbaikan Tata Letak Gudang TPS dengan Metode Class Based Storage di PT XYZ - Ahmad Jatnika Taryadi; Mumu Komaro; Wiku Larutama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Efficient warehouse layout management is a crucial factor in supporting smooth logistics operations. The Temporary Storage Warehouse (TPS) of PT XYZ currently applies a random storage system, resulting in high material handling distances, increased operational costs, and low space utilization. This study aims to redesign the warehouse layout using the class-based storage method combined with a block stacking system based on ABC analysis. The research method used is descriptive quantitative, with data collected through observation and interviews. The results show that the proposed layout reduces the material handling distance from 206,492 m/year to 147,970 m/year and decreases material handling costs from IDR 2,477,904 to IDR 1,775,640, achieving an efficiency of 28.34%. In addition, storage capacity increases from 250–300 packages to 400 packages. Therefore, the proposed warehouse layout design is proven to be more optimal in improving warehouse operational efficiency.